Regulation of Plasminogen Activator Inhibitor-1 mRNA in Human Endothelial Cells - Berg, E A van den; Sprengers, E D; Jaye, M; Burgess, W; Maciag, T; Hinsbergh, V W M van (Thrombosis and Haemostasis, 1988)
The plasminogen activator inhibitor (PAI-1) from endothelial cells is a potentially important regulator of plasminogen activator activity. Cultured human endothelial cells increase their PAI-1 production upon stimulation with LPS and TNF, agents that are known to cause an increase in PAI-1 levels in vivo.We isolated a PAI-1 cDNA probe, and by RNA hybridization analysis studied the regulation of PAI-1 mRNA synthesis in human endothelial artery cells. Freshly isolated endothelial cells do not contain detectable amounts of PAI-1 mRNA, but after adherence and incubation for 18 h in growth medium produce considerable amounts of PAI-1 activity and contain PAI-1 mRNA levels comparable to those found in subcultured cells. When subcultured endothelial cells are incubated for 6 h with LPS or TNF, both species of PAI-1 mRNA increase 10 to 20 fold, while PAI-1 activity in the growth medium increases only 1.5 to 2 fold. Stimulation of endothelial cells in the presence of cycloheximide (CHX) results in superinduction of mainly the 3.0 kb PAI-1 mRNA. The 3' end of this mRNA contains a 60 bp AT-rich sequence, that resembles 3' sequences present in a number of other genes superinducible with CHX.
Keywords: Endothelial cells; Plasminogen-activator inhibitor; Messenger RNA; Tumor necrosis factor; Endotoxin